NIGERIA: CORRUPTION ARISING FROM BAD LEADERSHIP - Anthony Eniayejuni; Nusret Sinan Evcan (European Scientific Journal, ESJ, 2015)
In Nigeria, Corruption has become the normal routine of successive government. The increasing rate of corruption is intrinsically interwoven with leadership problem. Since the early days of independence, the successive leaders have performed below expectation; they have been more concerned with accumulation of wealth rather than development of the country. Considering the large amount of human and natural resources, and the unlimited opportunities and possibilities that abound in the country, instead of bringing the much needed development and building institutions that will improve the lives of the people, these leaders have succeeded in exploiting and impoverishing the masses and have caused a colossal waste of natural and human resource. This paper argued that one of the factor that enhances and encourages corruption in Nigeria is lack of good and sincere leadership